2020
DOI: 10.1021/acs.analchem.0c03481
|View full text |Cite
|
Sign up to set email alerts
|

Automated Chiral Analysis of Amino Acids Based on Chiral Derivatization and Trapped Ion Mobility–Mass Spectrometry

Abstract: A fast and fully automated method for chiral analysis has been developed by combining a chiral derivatization approach with high-resolution trapped ion mobility separation. Although the presented approach can be potentially applied to diverse types of chiral compounds, several benchmark amino acids were used as model compounds, focusing on the smallest amino acid alanine. An autosampler with an integrated chromatography system was used for inline chiral derivatization with (S)-naproxen chloride and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…(S)-naproxen chloride ((S)-NAP) chiral derivatization of amino acids and TIMS-MS analysis was employed by Will's group [125]. Interestingly, the authors coupled an integrated chromatography system (ICS) to a TIMS-MS instrument.…”
Section: Separation Of Diastereomers After Cda Labelingmentioning
confidence: 99%
“…(S)-naproxen chloride ((S)-NAP) chiral derivatization of amino acids and TIMS-MS analysis was employed by Will's group [125]. Interestingly, the authors coupled an integrated chromatography system (ICS) to a TIMS-MS instrument.…”
Section: Separation Of Diastereomers After Cda Labelingmentioning
confidence: 99%
“…28 A recent study by Karst et al successfully demonstrated the enantioseparation of eight proteinogenic AAs by chiral derivatization with (S)naproxen chloride (S-NAP) using TIMS−MS. 29 Despite continuous advances in chiral derivatization coupled with IM−MS, the resolution and sensitivity for simultaneous determination of all chiral proteinogenic AA enantiomers in a single analytical run can still be improved. To unlock the critical bottleneck, designing a universal chiral selector is especially important.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, a number of analytical methods including liquid chromatography (LC), , gas chromatography (GC),and capillary electrophoresis (CE) coupled with ultraviolet (UV), fluorescence (FL), and mass spectrometric (MS) detections have been developed for the targeted chiral analysis of HAs/AAs. Besides chromatographic techniques, ion mobility-mass spectrometry (IM-MS) has also been emerged as a promising method for gas phase chiral analysis of AAs. To achieve separation, these methods employ either chiral derivatizing reagents (CDRs) or chiral stationary phases (CSPs). Recently, Takayama and co-workers proposed an efficient LC coupled with electrospray-ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF/MS) strategy for chiral metabolomics using selectively synthesized CDRs for different functional groups such as (S)-1-(4,6-dimethoxy-1,3,5-triazin-2-yl)­pyrrolidin-3-amine (DMT-3­(S)-Apy) for carboxylic acids and (S)-2,5-dioxopyrrolidin-1-yl-1-(4,6-dimethoxy-1,3,5-triazin-2-yl) pyrrolidine-2-carboxylate (DMT-(S)-Pro-OSu) for amines. , Although this methodology provides an extremely useful tool for chiral metabolomics, the requirement of different CDRs and derivatization protocols for each class of chiral metabolites limits its suitability for analyzing patient samples due to the limited amount of sample as well as the trace levels of enantiomeric forms that are typically present.…”
mentioning
confidence: 99%